Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s12875-018-0777-7
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction and stressors for working in out-of-hours care – a pilot study with general practitioners in a rural area of Germany

Abstract: BackgroundChallenging work environment, high workload, and increasing physician shortages characterize current rural general practice in Germany and in most European Countries. These factors extend into Out-Of-Hours Care (OOHC). However, little research about potential stressors for general practitioners (GPs) in OOHC settings is available. This pilot study aimed to evaluate workload, different elements of job satisfaction and stressors for GPs in OOHC and to analyze whether these aspects are associated with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
0
16
1
1
Order By: Relevance
“…More than half of GPs (51.6%) reported higher levels of job satisfaction. The rate of high job satisfaction in the current study is in the middle of reporting rates found in developed countries (e.g., Germany (42%) [ 43 ] and Canada (72%)) [ 44 ].…”
Section: Discussionmentioning
confidence: 49%
“…More than half of GPs (51.6%) reported higher levels of job satisfaction. The rate of high job satisfaction in the current study is in the middle of reporting rates found in developed countries (e.g., Germany (42%) [ 43 ] and Canada (72%)) [ 44 ].…”
Section: Discussionmentioning
confidence: 49%
“…In 2012 about 15% patients walked in an OOHC center without an appointment. New evaluations after the introduction of the national emergency number focusing on that percentage are not yet available [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The GP workforce in the United Kingdom (UK) is insufficient to meet current demand [2]. In addition, there is a dramatic shortage of GPs in Germany, especially in rural areas [3], and more than half of physicians (57%) contemplated leaving general practice in New Zealand [4]. Among key steps aimed at addressing these shortages include increases in recruitment and retention of GPs and to greater user of other health professionals [5].…”
Section: Introductionmentioning
confidence: 99%